Research Paper Based on Artifial Intelligence Chatbot - Zaira Zaid, Sachin Jain, Blessy Thankachan (Mathematical Statistician and Engineering Applications, 2023)
A chat-bot is a piece of software designed to simulate human-to-computer communication through the use of natural language. Chat-bots converse with customers in a conversation based on human input and provide customer service. Even though they are actually conversing with a machine, it gives the user the impression that they are speaking with a human. The chat bot programme enables students to learn about the college admissions process from any location with an internet connection and to get prompt responses. This chatbot system lessens the workload of the admission process department by giving the necessary information to the students or parents, as well as the department's workload to continue to answer all of the questions of the students.